The Effect of Fluconasole Prophylaxis on Lipid Peroxidation and Nitric Oxide, In Patients Operated For Mechanical Intestinal Obstruction (Annals of Medical Research, 2021)
None
Keywords: Mechanical intestinal obstruction, Fluconazole, Nitric oxide, TBARS